Repeated forced swim exacerbates methamphetamine-induced neurotoxicity: Neuroprotective effects of nanowired delivery of 5-HT3-receptor antagonist ondansetron - Lafuente J.V.; Sharma A.; Muresanu D.F.; Ozkizilcik A.; Tian Z.R.; Patnaik R.; Sharma H.S. (My University, 2025)
The possibility that stress associated with chronic forced swim (FS) may exacerbate methamphetamine (METH) neurotoxicity was examined in a rat model. Rats were subjected to FS in a pool (30 °C) for 15 min daily for 8 days. Control rats were kept at room temperature. METH was administered (9 mg/kg, s.c.) in both control and FS rats and allowed to survive 4 h after the drug injection. METH in FS rats exacerbated BBB breakdown to Evans blue albumin (EBA) by 150 to 220% and[131]-Iodine by 250 to 380% as compared to naive rats after METH. The METH-induced BBB leakage was most pronounced in the cerebral cortex followed by the hippocampus, cerebellum, thalamus, and hypothalamus in both FS and naive rats. The regional BBB changes were associated with a reduction in the local cerebral blood flow (CBF). Brain edema was also higher by 2 to 4% in FS rats after METH than in naive animals. Neuronal and glial cell injuries were aggravated by threefold to fivefold after METH in FS than the control group. Pretreatment with ondansetron (1 mg/kg, i.p.) 30 min before METH injection in naive rats reduced the brain pathology and improved the CBF. However, TiO2-nanowired delivery of ondansetron (1 mg/kg, i.p.) was needed to reduce METH-induced brain damage, BBB leakage, reduction in CBF, and edema formation in FS. Taken together, these observations are the first to show that METH exacerbates BBB breakdown leading to neurotoxicity in FS animals. This effect of METH-induced BBB breakdown and brain pathology in naive and FS rats is attenuated by ondansetron treatment indicating an involvement of 5-HT3 receptors, not reported earlier. © Springer Science+Business Media New York 2016.